EFFECT OF BIOFERTILIZERS AND SALICYLIC ACID ON CHEMICAL AND QUALITY SPECIFICATIONS IN PODS OF BEAN UNDER IRRIGATED WITH SALINE WATER - & et al., Majeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The experiment aimed to study the interactive effect between biofertilizers and salicylic acid on pods quality specifications and N,P,K,Fe and Mn concentrations in pods of bean plants under river and drainage water irrigation. The experiment Carried out using Spilt-Spilt-Plot Design using irrigation as the main plot , salicylic acid as sub plot , bio-fertilizers as sub-siplt-plot.  The triple combination among river water, biofertilizers mixture and 0.5mM salicylic acid recorded highest values in the percentage of carbohydrate (20.10 and 20.83%) dry meter(13.22 and 12.44%) TSS (11.65 and 10.09%) percentage of oils (0.59 and0.56%) protein(20.19 and 19.00%) Nitrogen (3.23 and 3.04%) Phosphorus (0.73 and 0.69%) and concentration of Iron (65.00 and 63.00 mg/kg-1) Manganese (13.50 and 14.17 mg/kg-1). The same treatment achieved the lowest values in pod fiber percentage (7.58 and 5.88 %) and  nitrate concentrations (137.2 and 146.6 mg/kg-1) . Treatment of river water, biofertilizers mixture and 1.0 mM salicylic acid achieved the lowest values in sodium (0.17 and 0.15%) and Chloride percentage  (1.10 and 1.05%) and highest value in potassium percentage (1.60 and 1.56)  for the tow growing season respectively.